The Effect Of Giving Education With Interactive Audio Visual Media On Compliance In Taking Medication In Pulmonary Tuberculosis Patients - La Joni; Haerudian Lahasani; Verawati Parhusip; Rari Nurhandayani; Antha Badrun Meram (Journal of Health Science Community, 2025)
The high level of mobility and population density has caused the spread and death from tuberculosis to increase. The purpose of this study was to evaluate the effectiveness of providing Health Education with Interactive Audio Visual Media on medication adherence in tuberculosis patients at Kaimana Hospital in the period of August 2024. The design of this study was a quasi-experiment with a non-randomized control group pretest-posttest design. The sampling method used purposive sampling with the specified criteria, 5 respondents in the control group and 5 respondents in the intervention group. The results of the study were tested using the Wilcoxon and Mann-Whitney tests, showing that there was a significant difference in adherence in pulmonary tuberculosis patients before and after the provision of Health Education using interactive audio visual media. Efforts to increase medication adherence in pulmonary tuberculosis patients at Kaimana Hospital through the provision of health education interactive audio visual media showed a significant increase.